2020
DOI: 10.48044/jauf.2020.008
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Women’s Preferences for Landscape Spatial Configurations and Relevant Socio-Economic Variables

Abstract: People’s preferences for urban parks are influenced by the spatial and contextual characteristics of spaces, where landscapes form the main body of parks. The present study examined women’s preferences for landscape spatial quality indicators (including coherence, mystery, complexity, legibility, prospect, and refuge) in two urban parks. Also, the study explored the impact of socio-economic variables such as age, income, and education on women’s preferences. In this spirit, a photo survey was conducted among 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In another study in Tabriz, Iran, perceptual preferences for plants (trees, shrubs, and flowers) showed growing trend with increases in education [44]. This increasing pattern was also detected for perceptual preferences for planting designs [45]. Formal education leads to an increase in self-confidence and awareness, and thus higher perception of social cohesion and security.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In another study in Tabriz, Iran, perceptual preferences for plants (trees, shrubs, and flowers) showed growing trend with increases in education [44]. This increasing pattern was also detected for perceptual preferences for planting designs [45]. Formal education leads to an increase in self-confidence and awareness, and thus higher perception of social cohesion and security.…”
Section: Resultsmentioning
confidence: 77%
“…Further, studies found the impact of personal characteristics on perception of design and aesthetic features. Studies demonstrated that women's age, income, and education affect their perceptual preferences for landscape elements [44], and spatial configuration [45].…”
Section: Personal Characteristics and Perceptionmentioning
confidence: 99%